Indigenous Post-Secondary Institutes in British Columbia, Canada: Exemplars of Indigenous Control over Indigenous Education - Robinson, Rheanna (Canadian Journal of Education/Revue canadienne de l'éducation, 2023)
Indigenous post-secondary institutes are a significant topic of study when considering Indigenous learners, Indigenous knowledges, and Indigenous self-determining efforts in places of higher education. Profiling three of these institutes in British Columbia, this article describes the promises and challenges they experience when weaving Indigenous knowledges into the academy. Using Indigenous and Western theory to support a case study design, semi-structured interviews were conducted with 22 participants including Elders, academic leaders, instructors, staff, and current/former students. Four prominent themes emerged regarding Indigenous post-secondary institutes: (1) Elders have a core role in supporting the integration of Indigenous knowledges, (2) the institutes impact Indigenous identity and a sense of belonging in the academy, (3) they lead in partnership and relationship building, and (4) they demonstrate resiliency despite systemic challenges. This study offers an important understanding of how Indigenous post-secondary institutes exemplify Indigenous control of Indigenous education while simultaneously modelling decolonization and reconciliation in higher education.